Synthesisof Zirconium Containing Mesoporous Material for the Efficient Catalytic Esterification of Benzyl Alcohol and Acetic Acid (Global Journal of Science Frontier Research, 2016)
This research focuses on the synthesis of metal-containin gmesoporous silica for catalytic esterification of benzyl alcohol with acetic acid. In this study Zr-containing MCM-41 with different molar ratios of Si/Zr were synthesized successfully. It is observed that the structural ordering of Zr-MCM-41varies with the Si/Zr ratio, and highly ordered mesoporous molecular sieves could be obtained for a Si/Zr molar ratio larger than 5. Calcination may significantly improve the structural regularity. In esterification reaction of benzyl alcohol with acetic acid, the benzyl alcohol conversion over all the Zr-MCM-41catalysts linearly increases with increasing the reaction temperature and selectivity to benzyl acetate was 100 %. The molar ratios of reactants also were investigated for final product yield; the molar ratio of acetic acid to benzyl alcohol can be 2:1 for high yield.
Keywords: Zr-MCM-41; benzyl alcohol; acid acetic; esterification; calcinations